Caracterización psicosocial de las familias del barrio 20 de Julio municipio de Urrao Antioquia (2009)
This article shows the results of a research carried out by Saint Bonaventure University, Medellin, in the “20 de Julio” Neighborhood in the Municipality of Urrao, Antioquia. It was a descriptive-retrospective study in which families and young people took part, as well as five institutions which have served directly to the community.The purpose of the study was to characterize the population of the neighborhood, in order to identify the current factors which interfere with cohabitation. The results described in the characterization of the families are grouped into: socio -demographic characteristics, time of living in the neighborhood, place of origin, and the reasons which led these families to live in the neighborhood, family make-up and dynamic, the housing conditions in general and the perception the family has about the problems which affect the neighborhood. Lastly, a discussion and the conclusions about the findings are presented